David W. Foster, Violence in Argentine literature. Cultural responses to tyranny. University of Missouri Press, Columbia, Missouri, 1995; 208 pp. - Zubieta, Ana María (El Colegio de México, 1998)
Se reseñó el libro: Violence in Argentine literature. Cultural responses to tyranny.